Antioxidant Effectiveness of Transparent Solid Soap from Red and White Pomelo (Citrus grandis (L.) Osbeck) Extracts - Septi Noiman Lase; Eva Sartika Dasopang; Supomo; Sumardi (Jurnal Indah Sains dan Klinis, 2024)
Background: Pomelo (Citrus grandis (L.) Osbeck) contains limonoids, flavonoids, naringin, and lycopene, which enhance the effects of ascorbic acid (vitamin C) in the body. Objective: This study aims to determine whether the extracts from red and white varieties of pomelo possess antioxidant properties and can be formulated into transparent solid soap that meets the quality standards set by SNI 3235-2016. Method: This experimental research utilized extracts from red and white varieties of pomelo. The research stages included sample preparation, processing of test materials, formulation of transparent solid soap with the addition of the extracts, and evaluation tests including organoleptic tests, pH tests, foam height tests, moisture content tests, and antioxidant activity tests using the DPPH method measured with UV-VIS spectrophotometry at concentrations of 60 μg/ml, 50 μg/ml, 40 μg/ml, 30 μg/ml, and 20 μg/ml. The results showed that both red and white pomelo extracts contain the same groups of compounds, including alkaloids, tannins, steroids, triterpenoids, and ascorbic acid. Results: Antioxidant tests indicated that the red pomelo extract has "moderate" antioxidant activity with an IC50 value of 185.086 μg/ml, while the white pomelo extract is "inactive" with an IC50 value of 564.309 μg/ml. The transparent solid soap exhibited "moderate" antioxidant activity with an IC50 value of 206.592 μg/ml. Conclusion: The transparent solid soap with red pomelo extract showed "weak" antioxidant activity with an IC50 value of 295.531 μg/ml, and the soap with white pomelo extract was "inactive" with an IC50 value of 130.207 μg/ml. The evaluation results for the transparent solid soap, including organoleptic properties, pH, foam height, and moisture content, conformed to the standards set by SNI 3235-2016